Production of docosahexaenoic acid, DHA using different modes of cultivation by Aurantiochytrium sp. SW1 - Shariffah Nurhidayah Syed Abdul Rahman; Mohd Sahaid Kalil; Aidil Abdul Hamid (Penerbit Universiti Kebangsaan Malaysia, 2021)
Thraustochytrids, such as members of the genus Aurantiochytrium, are rich in docosahexaenoic acid (DHA, C22:6n-3) and represent a promising source of omega-3 fatty acids which plays a vital role in the enhancement of human health, particularly for neurological and visual functions. Different modes of cultivation (batch, fed-batch and repeated-batch) by Aurantiochytrium sp. SW1 were studied for effective docosahexaenoic acid (DHA) production. In this study, three different modes of fermentation were carried out in 1 L shake flasks with a working volume of 500 mL, incubated at 30 ºC and 200 rpm. Batch cultivation significantly exceeds the rest of cultivation modes, achieving maximal lipid and DHA concentrations of 11.22 g/L and 5.87 g/L, respectively, and DHA productivity of 0.061 g/L/h. Lipid and DHA concentration of the repeated-batch process decreased through the cycles for all three different types of replacement ratio (80, 90 and 95%). The average decrease percentage of DHA concentration for cycle one and cycle two were 21.76 and 32.52%, respectively. However, the fatty acid composition of lipids obtained in the cycles remained consistent with 16:0 and DHA being the most abundant fatty acids indicating that this mode of fermentation is highly useable for industrial applications.